The Brokenwood mysteries. Series 1 [videorecording (DVD)] - Rea, Neill, 1971-; Sutherland, Fern (Acorn, 2015)
Detective Inspector Mike Shepherd arrives on assignment in Brokenwood, a small town where memories--and animosities--run deep. He's an experienced cop with a 1971 "classic" car, a collection of country music cassettes, and an indeterminate number of ex-wives. The new woman in his life is his assistant, Detective Constable Kristin Sims a by-the-book investigator nearly twenty years younger than her boss's car, who quickly has to get used to his lone-wolf ways.